EFFECT OF INFLUENZA VACCINES ON SUBPOPULATIONS OF BLOOD DENDRITIC CELLS - E. A. Chromova; E. A. Akhmatova; S. A. Skhodova; I. A. Semochkin; V. G. Khomenkov; N. K. Akhmatova; M. P. Kostinov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2016)
Aim. Study the effect of Vaxigrip split, Influvac subunit and Grippol plus immune-adjuvanted vaccines on the content of myeloid (mDC) and plasmacytoid (pDC) dendritic cells (DC) in blood of vaccinated healthy women. Materials and methods. Blood of 30 healthy women aged 18-50 years was studied at days 7 and 30 after the vaccination. pDC (CD14+CD16-/CD85k(ILT3)-PE/ CD123-PC5) and mDC (CD14+CD16-/CD85k(ILT3)-PE/CD33-PC5) immune phenotyping was carried out using mAbs (Beckman Coulter, France) and flow cytometer Cytomix FC-500 (Beckman Coulter, USA). Results. Use of unadjuvanted vaccines Vaxigrip and Influvac resulted in an increase of the numbers of mDC and pDC (p